Dance Teaching Activities in the Context of Informatization. Issue 2 (April 2021) - Chen, Yanmin
Abstract: In the context of the rapid development of the Internet in the information age, the deepening of resource sharing concept and the enhancement of information reform awareness in the field of higher education have played a catalytic role in the development of MOOC and the rise of SPOC. This paper mainly studies the design of dance teaching activities under the background of informatization. This paper makes full preparations for the model construction and teaching design by using the preliminary analysis, and at the same time synthesizes the curriculum foundation of many subjects involved in the teaching of physical dance, and chooses the professional course of physical dance as the medium for the next teaching experiment. In the teaching effect verification based on summative evaluation, 40 students majoring in dance performance in an art college were selected as experimental objects, and SPSS22.0 software was used to test homogeneity within and between the experimental group and the control group, respectively. It is feasible to apply the MOOC+SPOC based hybrid teaching mode to the external conditions, internal motivation, emotion and other support of sports dance teaching in universities.